Distal Nerve Transfers: A Perspective on the Future of Reconstructive Microsurgery - Chuang, David Chwei-Chin (Journal of Reconstructive Microsurgery, 2018)
Background Nerve transfer can be broadly separated into two categories: proximal nerve graft and/or transfer and distal nerve transfer. The superiority of proximal nerve graft/transfer over distal nerve transfer strategy has been debated extensively, but which strategy is the best has not yet been defined. Each technique has its own advantages and disadvantages. However, proximal nerve graft/transfer is still the main reconstructive procedure based on the principle of “no diagnosis, then no treatment.” Proximal nerve transfer can avoid iatrogenic injury where the lesion is still in continuity and neurolysis is the only procedure without further cutting the nerve.Results Our clinical and experimental study show that proximal nerve grafts/transfers yield at least equal or better results compared to distal nerve transfers. Proximal nerve grafts/transfers remain the mainstay of my reconstructive strategy. Proximal nerve graft/transfer offers more accurate diagnosis and proper treatment to restore shoulder and elbow functions simultaneously. Distal nerve transfers can offer more efficient elbow flexion.Conclusion Combined, both strategies in primary nerve reconstruction are especially recommended when there is no healthy or not enough donor nerve available Distal nerve transfers should be considered as a complementary option for proximal nerve grafts/ transfers.
Keywords: brachial plexus injury; distal nerve transfer; proximal nerve transfer; level of brachial plexus injury